Bomber Planes - Schleifer, Jay. (Minneapolis : Capstone Press, 1996)
Describes the design of various types of bombers, their uses in combat, and their role in the future.
Includes bibliographical references (p. ) and index.
Keywords: Bombers -- Juvenile literature; Bombing, Aerial -- Juvenile literature; Bombers; Airplanes, Military